The Effect of VAK (Visualization, Auditory, Kinesthetic) Learning Model Assisted by Baamboozle Game on the Mathematical Communication of Grade VIII Students at SMP Negeri 2 Sumpiuh - Carribia, Nevada; Anter, Maria Cristine Joy V. (International Journal of Research in Mathematics Education, 2025)
This research was conducted because it was motivated by the low mathematical communication skills of class VIII students of SMP Negeri 2 Sumpiuh. With this low mathematical communication skills of class VIII students, based on the preliminary test conducted, a solution is needed. The purpose of this study was to determine whether there was an effect of the VAK (Visualization, Auditory, Kinesthetic) learning model assisted by the Baamboozle Game on the mathematical communication of grade VIII students at SMP Negeri 2 Sumpiuh. This study used quantitative experimental design research. This experimental design uses a quasi-experiment. This study has a population of 271. The research sample was class VIII D as the experimental class and class VIII B as the control class. The analysis of this study used the N-Gain test and the t-test. The results of this study indicate that the experimental class obtained an average N-Gain value of 0.6491, which means that the learning model in the experimental class is quite effective, while the control class obtained an average N-Gain value of 0.3661, which means that the learning model used is not effective. Then, based on the t-test calculation, on the N-Gain value between the two sample classes, a significant value of 0.000 <0.05 was obtained. It can be concluded that there is a difference in the average N-Gain value of the experimental class and the control class. so that there is an effect of the VAK (Visualization, Auditory, Kinesthetic) learning model assisted by the Baamboozle Game on the mathematical communication of grade VIII students at SMP Negeri 2 Sumpiuh